2005
DOI: 10.1103/physreve.72.036113
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal impedances and the Casimir entropy at low temperatures

Abstract: The problem with the temperature dependence of the Casimir force is investigated. Specifically, the entropy behavior in the low temperature limit, which caused debates in the literature, is analyzed. It is stressed that the behavior of the relaxation frequency in the T-->0 limit does not play a physical role since the anomalous skin effect dominates in this range. In contrast with the previous works, where the approximate Leontovich impedance was used for analysis of nonlocal effects, we give description of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 46 publications
5
96
0
Order By: Relevance
“…Furthermore, in the large-distance limit the matrix elements of the roundtrip operator are very small and we may expand the logarithm in (7). In view of tr(A) = log[det(exp(A))] with tr denoting the trace, we then obtain…”
Section: Large-distance Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the large-distance limit the matrix elements of the roundtrip operator are very small and we may expand the logarithm in (7). In view of tr(A) = log[det(exp(A))] with tr denoting the trace, we then obtain…”
Section: Large-distance Approximationmentioning
confidence: 99%
“…During the last decade or so various papers have focused on the entropy related to the Casimir interactions between two solid bodies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. An important reason for this interest lies in the fact that the Casimir entropy can reach negative values.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior seen in the previous figures indicates significantly different entropies for the surface models, with a strong dependence on the presence of dissipation (conductivity) at low frequencies. This parallels the discussion of the macroscopic Casimir entropy for the dispersion interaction between two plates, a subject of recent controversies, where the Drude and plasma models give different answers [43,[63][64][65][66][67]. The results that follow indicate that the magnetic Casimir-Polder interaction may provide an alternative scenario to investigate this point.…”
Section: Atom-surface Entropymentioning
confidence: 62%
“…[65,66] it has been shown that not only dissipation but also nonlocality of the response has strong implications for the entropy. In particular, the residual entropy ∆S = 0 vanishes, because at very low temperatures, the anomalous skin effect and Landau damping take the role of a nonzero dissipation rate.…”
Section: Atom-surface Entropymentioning
confidence: 99%
“…It should be noted that on the molecular level the permittivity becomes non-local, ε = ε(ω, k), where k is the magnitude of the wave vector k. Then ε becomes finite for finite k. Only the special case ε(0, 0) is infinite, and this ("measure zero") can not be expected to give a finite contribution to the Casimir force. In independent studies Svetovoy and Esquivel [6] and Sernelius [7] find that the TE zero mode should not contribute when spatial dispersion is carefully taken into account. Because of nonlocal effects, the former of these state, "the question does [ν] go to zero or have some residual value at T → 0 becomes unimportant" and they find that the TE zero frequency contribution must indeed be zero to satisfy Nernst's theorem.…”
mentioning
confidence: 99%